Factors associated with unsuccessful pessary fitting and reasons for discontinuation in Korean women with pelvic organ prolapse - Sumin Oh; Hye Ryun Namkung; Hee Yeon Yoon; So Yeon Lee; Myung Jae Jeon (Korean Society of Obstetrics and Gynecology, 2022)
Objective To identify the factors associated with unsuccessful pessary fitting and reasons for pessary discontinuation in Korean women with pelvic organ prolapse (POP). Methods The medical records of 234 patients who underwent pessary fitting for the management of symptomatic POP were retrospectively reviewed. A ring pessary with or without support was used. Successful pessary fitting was defined as the ability to wear a pessary for 2 weeks without any discomfort. Factors associated with unsuccessful pessary fitting were determined using a multivariable logistic regression analysis. A Kaplan-Meier survival curve was obtained to examine the probability of continuing pessary use over the follow-up period. The reasons for the discontinuation of pessary were identified. Results Two-hundred-and-twenty-five women were included in the analysis. The rate of unsuccessful pessary fitting was 40%. Prior hysterectomy (odds ratio [OR], 4.13; 95% confidence interval [CI], 1.81-9.42) and POP quantification stage III-IV (OR, 2.49; 95% CI, 1.28-4.85) were independent risk factors for unsuccessful pessary fitting. Among the patients with successful pessary fitting, the median time to discontinuation of pessary use was 4 years. The most common causes of discontinued use were vaginal erosion (45.3%) and urinary incontinence (26.5%). Conclusion Patients with a history of hysterectomy and advanced-stage POP are at risk for an unsuccessful fitting of the ring pessary. Vaginal erosion is the main reason for discontinued use among patients with successful pessary fitting.